Nonlinear Backstepping Fault-Tolerant Controllers with Extended State Observers for Aircraft Wing Failures - Yansheng Geng; Bo Wang; Xiaoxiong Liu (Actuators)
To effectively overcome changes in aircraft aerodynamic and control characteristics caused by wing surface damage, this paper proposes a fault-tolerant control method based on an extended state observer (ESO) to ensure flight mission requirements under wing surface and control surface failures. First, considering the characteristics and requirements of backstepping control in addressing nonlinear problems, an extended observer is designed to estimate disturbances and uncertainties induced by wing surface failures, and its stability is analyzed by using the Lyapunov method. Next, a backstepping control law for the airflow angle loop is designed based on the extended observer. The serial-chain method is introduced as an allocation algorithm for fault-tolerant flight control in order to compensate for the changes in control efficiency caused by wing surface faults. And stability analysis is conducted by integrating the control characteristics of the aircraft’s airflow angle loop, proving the uniformly bounded stability of the controller. Finally, fault-tolerant control simulations are performed under scenarios of wing damage, elevator damage, and actuator jamming faults. The simulation results demonstrate that the proposed method achieves excellent control performance during wing surface failures.